Партийная система в Турецкой Республике в 1930-1945 гг. - Багдасарян, Сурен («Զանգակ - 97»)
The problem of the forming of the party system and its role in the initiation, managing and consolidation of the dynamic political changes is one of the main questions in the investigation of the historical and political processes. In the Turkish Republic at 1920s was formed the one-party system in which dominatcd one powerfiil force and the most organized Institution — Republican People Party.
Keywords: История; Турция